Shoreline rehabilitation for recreation and ecological functionality - Ramage, Dylan (Kansas State University, 2023)
Pottawatomie State Lake No. 2 is a recreational lake near Manhattan, Kansas that attracts families and anglers to enjoy a variety of activities such as fishing, camping, and picnicking. Unfortunately, the lake is showing signs of erosion and degradation near the shorelines which poses ecological concerns for aquatic species like the Largemouth Bass and accessibility and safety concerns for the site’s visitors. This report aims to spotlight the importance of rehabilitating shorelines to create connections between aquatic habitat, shoreline access, camping, and day-use programming along recreational lakes in the Flint Hills Ecoregion of Kansas. With the long-term goal of establishing Pottawatomie State Lake No. 2 as a future precedent for similar lakes, this report explores design guidelines and a projective design for the site. This report builds on research about naturalized shorelines and aims to fill the gaps between the human recreation and the ecological functionality of manmade lakes. To achieve this result, this report includes a literature review, site analysis, precedent studies, design guidelines, and a projective design. By conducting these methods of research, this project shows how to create naturalized shorelines that improve aquatic habitat for Largemouth Bass while wisely addressing the need for human recreation near the water’s edge at Pottawatomie State Lake No. 2.
Keywords: Shoreline rehabilitation; Landscape architecture; Largemouth Bass; Recreation; Vegetative buffers; State parks